Agenda-Setting Theory in Mass Communication: The Influence of Media on Issue Prioritization in Society - Priscilla, May; Afdhalu, Muhammad; Yulia, Davira; Amrullah, Muhammad Hafidz; Atmanegara, Xavira; Aprilia, Fatimah Zahra (Journal of Media and Digital Society on SDGs, 2025)
Agenda setting theory suggests that mass media has great power in determining issues that should be of public concern, by prioritizing certain topics and influencing how people view these issues. Along with the development of communication technology, especially the emergence of social media, the role of the media in shaping the public agenda has changed significantly. If previously traditional media such as television, radio, and newspapers played a dominant role in determining important issues, now social media allows audiences to be more active in the distribution and agenda-forming process, which introduces a new dimension in mass communication. This study aims to explore the application of agenda setting theory in the context of traditional media and social media, and to identify how both influence the formation of public opinion on contemporary issues, such as the 2020 US Presidential Election and the COVID-19 pandemic. This article uses a qualitative approach with a case study, where analysis is carried out on traditional media coverage and conversations on social media to observe the agenda setting patterns that emerged during the two major events. Using content and framing analysis, this study explores how issues reported by traditional media can be influenced or amplified by social media, as well as how the two types of media interact in shaping public perception and influencing public responses to events that occur. The findings of this study indicate that although social media offers greater space for public participation, traditional mass media still have a major role in directing public attention to certain issues, although in some cases, social media can accelerate the process of changing the agenda. Thus, this article concludes that the agenda setting theory remains relevant in understanding mass communication in the digital era, although adjustments are needed to understand the dynamics that occur in social media which are faster, more interactive, and full of challenges.